IMPLEMENTATION OF FREE STUDENT TRANSPORT POLICY IN THE CITY OF BANJARBARU - Ahmad Noor Suprayogie (JURNAL SOCIUS, 2022)
School or student transportation services is one form of special service management in the City of Banjarbaru. Since the launch of the Free Student Transport Program (APG) by the Mayor of Banjarbaru, the people of the City of Banjarbaru have been warmly welcomed, especially parents of students. However, this did not last long because their child was forced to return to using a motorbike. After all, the students were not transported by the free transportation provided by the Banjarbaru City Government. As a result, APG in Banjarbaru City has not run optimally until now. So it is necessary to know the needs, support, and constraints that affect the implementation of the Free Student Transport Policy. This study aims to analyze the community's needs, government and community support, and the obstacles that affect the implementation of the APG policy in the City of Banjarbaru. This research method uses qualitative methods through collecting data with the stages of observation, data reduction, data presentation, concluding, and interviews. The implementation of APG in Banjarbaru City does not provide safety insurance. There are two doors in the APG, a car type with student entry and exit; the door is still manual or cannot close automatically. The APG seat has a safety belt but is not used by students because the passengers exceed the capacity. The car (Travel A), the passenger seat facing left and right, does not have a safety belt (Track B); in the APG, there is no handle grip (hanging handle). In the operation of the APG, it is operated by one driver, and there is no other security/assistant officer. Unlike the bus type APG, all facilities are complete, the level of comfort and safety is guaranteed. The operation of APG is exclusively for the students.